Retail management : a strategic approach - Berman, Barry. (Prentice Hall, 1998)
This book has eight parts: An Overview of Strategic Retail Management, Situation Analysis, Targeting Customers and Gathering Information, Choosing A Store Location, Managing a Retail Business, Merchandise Management and Pricing, Communicating with the Customer, and Planning for the Future.